2021
DOI: 10.1016/j.mnl.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The Remote Influence of Nursing Leadership

Abstract: Maintaining connection and support of staff amid the unprecedented challenges of the coronavirus pandemic (COVID-19) was difficult. One nurse leader conscientiously sent "Monday morning messages" to assure consistent inspirational communication with staff. Although remote work caused the leader to be separated from the staff, these messages helped support them through adaption, change, progress, and promotion of resiliency. The ability to inspire is an essential leadership trait, invaluable in times of crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 3 publications
0
24
1
Order By: Relevance
“…The active presence of leaders provides opportunities for nurses to be supported in terms of their resilience and ability to thrive in their daily work (Daly et al, 2020). Additionally, there is a positive ripple effect of effective leadership and support that flows from leader to staff and beyond (Prestia, 2020). Our study findings reflect how this ripple effect can also be reciprocal in which the resilience of all of those involved, particularly in emotionally difficult situations such as those caused by the pandemic, is nurtured.…”
Section: Discussionmentioning
confidence: 58%
“…The active presence of leaders provides opportunities for nurses to be supported in terms of their resilience and ability to thrive in their daily work (Daly et al, 2020). Additionally, there is a positive ripple effect of effective leadership and support that flows from leader to staff and beyond (Prestia, 2020). Our study findings reflect how this ripple effect can also be reciprocal in which the resilience of all of those involved, particularly in emotionally difficult situations such as those caused by the pandemic, is nurtured.…”
Section: Discussionmentioning
confidence: 58%
“…Three of the research studies applied the quantitative and two qualitative methods. The studies addressed nurse leaders' resilience (Duncan, 2020 ; Jeffs et al, 2020 ) and their role in supporting nurses' resilience during the COVID‐19 pandemic (Abd‐EL Aliem & Abou Hashish, 2021 ; Berkow et al, 2020 ; Cariaso‐Sugay et al, 2021 ; Chesak et al, 2020 ; Dimino et al, 2020 ; Duncan, 2020 ; Heuston et al, 2021 ; Jeffs et al, 2020 ; Kreh et al, 2021 ; Leng et al, 2021 ; Markey et al, 2021 ; Prestia, 2021 ) (Table 1 ). The themes and subthemes identified from these articles are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Authentic, exemplary, ethical, and transformational leadership styles were presented to benefit nurse leaders in supporting nurses' resilience during the COVID‐19 pandemic (Abd‐EL Aliem & Abou Hashish, 2021 ; Dimino et al, 2020 ; Duncan, 2020 ; Jeffs et al, 2020 ; Leng et al, 2021 ; Markey et al, 2021 ; Prestia, 2021 ). The studies showed that crisis require nurse leaders to have a strong understanding of the situation as well as a visible leadership style (Dimino et al, 2020 ; Jeffs et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of guidance in completing the task and communication between leader and employees are allegedly one of the causes of low motivation. It is stated that leadership is an ability owned by someone to influence someone else to do a better work in order to achieve the goals of companies or organizations (Prestia, 2021). In addition, leadership is declared as a process conducted by a leader to influence, coordinate and guide another party in an organization or a company to achieve determined goals (Budiman & Barata, 2018).…”
Section: Stated That Performancementioning
confidence: 99%